1999
DOI: 10.1001/archotol.125.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Gustatory Sweating (Frey Syndrome) After Intracutaneous Injection of Botulinum Toxin Type A

Abstract: The present series demonstrated a linear regression in the effectiveness of the intracutaneous injection of botulinum toxin type A in patients with gustatory sweating, while no factors appeared to be statistically related to the duration of effectiveness and/or the incidence of recurrent gustatory sweating. However, because the severity of recurrent gustatory sweating is reduced when compared with the severity of the initial gustatory sweating and because recurrent gustatory sweating remains amenable to reinje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 8 publications
7
50
0
2
Order By: Relevance
“…In studies with a longer follow-up, the effectiveness was temporary and recurrence rate was higher. 20,41,43 However, because the severity of recurrent Frey syndrome is reduced when compared with the severity of the initial Frey syndrome and because recurrent Frey syndrome remains amenable to reinjection of botulinum toxin A, intracutaneous injection of botulinum toxin A is suggested to be the first-line treatment option in patients with Frey syndrome. 20,43 Botulinum toxin A treatment appears to be effective in almost all patients, minimally invasive, well tolerated and long-lasting (>6 months) and can be repeated.…”
Section: Treatmentmentioning
confidence: 99%
“…In studies with a longer follow-up, the effectiveness was temporary and recurrence rate was higher. 20,41,43 However, because the severity of recurrent Frey syndrome is reduced when compared with the severity of the initial Frey syndrome and because recurrent Frey syndrome remains amenable to reinjection of botulinum toxin A, intracutaneous injection of botulinum toxin A is suggested to be the first-line treatment option in patients with Frey syndrome. 20,43 Botulinum toxin A treatment appears to be effective in almost all patients, minimally invasive, well tolerated and long-lasting (>6 months) and can be repeated.…”
Section: Treatmentmentioning
confidence: 99%
“…Schulze-Bonhage et al [30], Bjerkhoel and Trobbe [4], Laccourreye et al [24] and Arad-Cohen and Blitzer [2] have confirmed the effectiveness of the treatment with their data. The longest follow-up was reported by Laccourreye et al [25] and exceeded a period of 3 years, demonstrating a linear regression in the effectiveness of BT, although no factors appeared to be statistically related to the duration of the result. On the other hand, the severity of the recurrent Frey's syndrome was diminished 20%-90% compared to the initial status.…”
Section: Discussionmentioning
confidence: 76%
“…One patient had transient facial paresis following BT treatment on day 3. Laccourreye et al 14 , in a follow-up study of 33 FS patients treated with BT, found recurrence rates of 27% in ther first year, 63% in the second and 92% in the thirdy year, by means of clinical assessment and Minor iodine-starch test. Nevertheless, patients reported prolonged improvement and recurrence remained amenable to reinjection of BT.…”
Section: Discussionmentioning
confidence: 97%